(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
This work sought to analyze the failure rates of two introductory subjects of the Licenciatura degree in Chemistry at the Federal Institute of Espírito Santo (IFES) - campus Vila Velha, through data collection from the academic system and also questionnaires with pass and fail students in the subjects in focus from 2016 to 2019. The subjects of General Chemistry I and Fundamentals of Elementary Mathematics have shown high failure rates and the results proved our hypothesis that the main difficulty is the lack of theoretical basis in high school. Thus, some educational strategies to mitigate retention are presented in this article.